An Evaluation of Insolvency and Its Causes in The Construction Industry - Reuben A. Okereke; Tobechi B. Ejekwu; Victor O. Ohamma (Three E Science Institute, 2021)
This study evaluated insolvency and determined its causes in the construction industry in Nigeria. The study utilized a questionnaire as the research instrument with a sample size of 90 contractors in Imo State, and descriptive statistics such as cross-tabulation and mean ranking were used to describe and summarize the data. In addition, a one-sample-test was employed to compare and find out the most significant issues that may cause insolvency in the construction industry. The study concludes that of the 11 potential causes of bankruptcies in the construction sector, the respondents listed five as main causes, absence of entry barriers, issues with cash flow, poor financial monitoring, knock-on consequences, and onerous contract terms. The study recommends that ethical actions and procedures be considered for the construction industry and main vendors to prevent jeopardizing the financial stability of supply chain contractor firms.